Impact of Coronary Artery Disease on 30‐Day and 1‐Year Mortality in Patients Undergoing Transcatheter Aortic Valve Replacement: A Meta‐Analysis. Issue 10 (11th October 2017) - Sankaramangalam, Kesavan; Banerjee, Kinjal; Kandregula, Krishna; Mohananey, Divyanshu; Parashar, Akhil; Jones, Brandon M.; Jobanputra, Yash; Mick, Stephanie; Krishnaswamy, Amar; Svensson, Lars G.; Kapadia, Samir R.
Abstract : Background: The impact of coronary artery disease (CAD) on outcomes after transcatheter aortic valve replacement (TAVR) is understudied. Literature on the prognostic role of CAD in the survival of patients undergoing TAVR shows conflicting results. This meta‐analysis aims to investigate how CAD impacts patient survival following TAVR. Methods and Results: We completed a comprehensive literature search of Embase, MEDLINE, and the Cochrane Library, and included studies reporting outcome of TAVR based on CAD status of patients for the analysis. From the initial 1631 citations, 15 studies reporting on 8013 patients were analyzed using a random‐effects model. Of the 8013 patients undergoing TAVR, with a median age of 81.3 years (79–85.1 years), 46.6% (40–55.7) were men and 3899 (48.7%) had CAD (ranging from 30.8% to 78.2% in various studies). Overall, 3121 SAPIEN/SAPIEN XT/SAPIEN 3 (39.6%) and 4763 CoreValve (60.4%) prostheses were implanted, with transfemoral access being the most frequently used approach for the implantation (76.1%). Our analysis showed no significant difference between patients with and without CAD for all‐cause mortality at 30 days post TAVR, with a cumulative odds ratio of 1.07 (95% confidence interval, 0.82–1.40; P= 0.62). However, there was a significant increase in all‐cause mortality at 1 year in the CAD group compared with patients without CAD, with a cumulative odds ratio of 1.21 (95% confidence interval, 1.07–1.36; P =0.002). Conclusions: Even though coexisting CAD does not impact 30‐day mortality, it does have an impact on 1‐year mortality in patients undergoing TAVR. Our results highlight a need to revisit the revascularization strategies for concomitant CAD in patients with TAVR.